Proximal tubular dysfunction in pregnant women receiving tenofovir disoproxil fumarate to prevent mother-to-child transmission of hepatitis B virus. (19th January 2022) - Liegeon, Geoffroy; Ngo-Giang-Huong, Nicole; Salvadori, Nicolas; Bunpo, Piyawan; Cressey, Ratchada; Achalapong, Jullapong; Kanjanavikai, Prateep; Patamasingh Na Ayudhaya, Orada; Prommas, Sinart; Siriwachirachai, Thitiporn; Sabsanong, Prapan; Yves Mary, Jean; et al.
Abstract: Background: Data evaluating the risk of proximal tubular dysfunction in women receiving tenofovir disoproxil fumarate for the prevention of mother-to-child transmission (PMTCT) of HBV are scarce. Objectives: To assess the risk of proximal tubulopathy in pregnant women receiving tenofovir disoproxil fumarate for PMTCT of HBV. Patients and methods: We used urine samples collected from HBV monoinfected pregnant women who participated in a Phase III, multicentre, randomized, double-blind, placebo-controlled clinical trial assessing a tenofovir disoproxil fumarate short course from 28 weeks gestational age (28-wk-GA) to 2 months post-partum (2-months-PP) for PMTCT of HBV in Thailand. Markers of tubular dysfunction, including retinol binding protein, kidney injury molecule-1, α1-microglobuin and β2-microglobulin, were assayed at 28- and 32-wk-GA and 2-months-PP visits. Proximal tubulopathy was defined as the presence of ≥2 of the following: tubular proteinuria, euglycaemic glycosuria and increased urinary phosphate. Results: A total of 291 women participated in the study. No kidney-related adverse events were severe, and none led to tenofovir disoproxil fumarate discontinuation. At 2-months-PP, 3 of the 120 (3%) evaluated women in the tenofovir disoproxil fumarate group experienced proximal tubulopathy versus 3 of 125 (2%) in the placebo group ( P = 1.00). None of the six women met the criteria for proximal tubulopathy at 12-months-PP but proteinuria persisted in three of them. No growth abnormalities were found at 1 year of age in infants born to mothers with proximal tubulopathy at 2-months-PP. Conclusions: In these HBV-infected pregnant and breastfeeding women, tenofovir disoproxil fumarate administered from 28-wk-GA to 2-months-PP was not associated with a higher risk of proximal tubulopathy.